THE SIGNIFICANCE OF COLOR CHOICE IN AESTHETIC ALL-CERAMIC RESTORATIONS: A COMPARATIVE ANALYSIS BETWEEN CLINICIANS AND PATIENTS - Daniela Florizeta Mihali; Dan Lolos; Roxana Oancea; Adrian Jantea; Liliana Porojan; Loredana Mitariu; Mihai Mitariu; Dana Cristina Bratu; Cosmin Sinescu; Sorin Gheorghe Mihali (Romanian Society of Oral Rehabilitation, 2023)
This study aimed to assess patient satisfaction in relation to color choice for all-ceramic full-arch dental restorations. Additionally, the study aimed to compare satisfaction levels between colors selected by clinicians and those chosen by patients. A survey was conducted, supported by photo-graphic documentation taken before treatment, during the mock-up phase, and after the final res-torations were fixed. The study included 60 individuals who had undergone full-arch aesthetic treatments. The results revealed no statistically significant difference in patient satisfaction with the final restoration color based on whether it was chosen by the clinician or the patient. Notably, a higher level of patient satisfaction (90%) was observed when the clinician was responsible for color selection. Amidst the present societal influences, clinicians find themselves with a crucial responsibility of assisting patients in making suitable color choices throughout the diverse stages of the rehabilitation process.